Idea unii polsko-litewskiej w twórczości Jana Kochanowskiego - Rusnak, Radosław (Tematy i Konteksty, 2019)
The paper takes a common view of those works by Jan Kochanowski which reflect the relationship between the author and the act of the Polish-Lithuanian Union established on 1 July 1569 in Lublin. The only text that is the poet’s direct reaction to the event in question is Proporzec or Hołd pruski, which does not mean that there are no other works of this type by Kochanowski. The examples are the poem Zgoda / Concordia, Fragment XXI (Battle with Amurat at Varna), the Latin Ode IV (Ad Concordiam) or Fraszka II 107 (Na most warszewski / On the Bridge of Warsaw).